The contributions of socioeconomic status, perceived stress, and depression to disability in adults with systemic lupus erythematosus. Issue 9 (23rd April 2020) - Sumner, Lekeisha A.; Olmstead, Richard; Azizoddin, Desiree R.; Ormseth, Sarah R.; Draper, Taylor L.; Ayeroff, Julia R.; Zamora-Racaza, Geraldine; Weisman, Michael H.; Nicassio, Perry M.
Abstract: Purpose: Psychological and sociodemographic factors contribute to disability in systemic lupus erythematosus. Yet the pathways by which these factors influence disability remain unclear. The objective of this study was to evaluate a model examining socioeconomic status (SES), perceived stress, and depressive symptoms as determinants of lupus-related disability. Methods: The sample included 134 patients receiving treatment at an academic hospital. Structural equation modeling examined the direct and indirect effects of SES (income, education, and subjective social status), perceived stress (Perceived Stress Scale), and depressive symptoms (Hospital Depression Anxiety Scale depression subscale) on disability (Lupus Patient-Reported Outcome measure Physical Health and Pain-Vitality subscales). Results: Structural equation modeling confirmed that the model fit the data well. The SES exerted a direct negative effect on perceived stress (β = −0.40, p < 0.001). In turn, perceived stress predicted higher levels of depression (β = 0.72, p < 0.001), which ultimately contributed to greater disability (β = 0.53, p < 0.001). The influence of SES on disability was indirect (mediated by perceived stress and depression). Conclusions: Findings support the socioeconomic gradient in disability as mediated by perceived stress and depression, such that lower SES contributed to lupus-related disability via perceived stress and depressive symptoms. Implications for Rehabilitation: Low socioeconomic status, perceived stress, and depression are prognostic factors for the disability in systemic lupus erythematosus. Study findings indicate that perceived stress and depression fully mediate (account for) the negative impact of low socioeconomic status on lupus-related disability. Screening for and addressing psychological distress may enhance management of disability in lupus patients. This research demonstrates the value of a conceptual framework for identifying potentially modifiable risk factors for disability in lupus and other chronic disabling diseases.